Trend Citizen Journalism Dalam Membentuk Narasi Berita Pada Media Sosial Lampung Geh News - Istiani, Ade Nur; Syafira, Nanda; Nasution, Nadya Amalia (CV. ITTC INDONESIA, 2025)
The development of digital technology has given rise to the phenomenon of citizen journalism, which is transforming the traditional media ecosystem. This transformation creates new spaces for public participation in news production and distribution, but it also raises challenges related to the credibility and accuracy of information. Research on how citizen journalism shapes news narratives on local social media—particularly the interaction between platform algorithms, citizen participation, and information verification processes in the context of regional Indonesian media—remains limited. This study aims to explore citizen journalism trends on the Lampung Geh News platform and analyze their influence on the formation of news narratives on social media, as well as to identify the information verification strategies developed within the citizen journalism ecosystem. The research employs a qualitative approach using a case study method conducted from January to April 2024. Data were collected through in-depth interviews with two platform administrators and two citizen contributors of Lampung Geh News selected purposively, non-participant observation of social media content, and analysis of platform policy documents. The findings reveal three main points, increased public participation in digital public spaces through information contributions and comment section discussions, with an average engagement of 75–120 comments per post, social media algorithms significantly determine the visibility and popularity of certain news narratives, with highly engaged content receiving three times more exposure, and collaboration among citizens, media managers, and stakeholders in a four-stage information verification system. Although citizen journalism enriches local news perspectives and builds communication bridges with government stakeholders, issues of accuracy and credibility remain key concerns, necessitating the strengthening of digital literacy and the development of adaptive ethical standards.